Avaliação de vantagens, desvantagens e desafios da renaturalização do lago da Universidade Federal de São Carlos (São Carlos – SP) - Lustosa, Gustavo Ezequiel Delfino Pinto (Universidade Federal de São Carlos, 2021)
Landscapes with water bodies present ecological elements and processes that guarantee environmental quality and quality of life for the living beings that inhabit or frequent them. Anthropogenic interventions in these watercourses made throughout history, as exemplified by the construction of dams for different purposes, can bring both negative and positive impacts and, therefore, configure themselves as typical 'complex environmental problems'. Such is the case of “UFSCar Lake”, a symbol reservoir of the Federal University of São Carlos (UFSCar – São Carlos campus) formed by the damming of Monjolinho river, but which had to be drained in 2019 due to safety problems in its dam. Since then, alternatives for the water body have been studied, as in addition to the cost of renovating the dam being very high, the management related to it has also become very complex due to current legislation. Because of this, the alternative of renaturalizing Monjolinho river in São Carlos campus of UFSCar has been considered as an adequate solution to this problem. Therefore, this study aims to analyze the challenges, advantages and disadvantages associated with the possible renaturalization of UFSCar Lake in relation to ecosystem services, environmental impacts, safety and economic costs. Therefore, a bibliographical survey of the history of UFSCar Lake was carried out; and technicians, researchers and managers who are specialists in the topics covered in the work and/or were involved in the lake's drainage process were interviewed. The results obtained by crossing primary and secondary data indicated that the damming of the Monjolinho river generated negative impacts on its biota and on the quality of its water. On the other hand, the lake started to perform cultural ecosystem services and shelter a new adapted biota. However, due to the financial limitations and complexity of managing a dam due to recent legal changes, it is very costly for the university to maintain the dam. Therefore, the alternative for the renaturalization of Monjolinho river in the stretch where it crosses the UFSCar is promising, as it would not only be less costly and safer in the long term, it could reduce the environmental impacts generated by the dam as well as create a new symbol for the community. These conclusions are corroborated both by theoretical aspects and national and international examples already carried out in other rivers, as well as shared by the interviewees in this work.
Evaluation of advantages, disadvantages and challenges of the renturalization of lake at the Universidade Federal de São Carlos (São Carlos - SP)
Keywords: Córrego do Monjolinho; Barragem; Corpo hídrico; Problema ambiental complexo; Renaturalização; CIENCIAS BIOLOGICAS